Sustainable Harvesting of the Ecosystem Engineer Corallina officinalis for Biomaterials - Magill, Caroline L.; Maggs, Christine A.; Johnson, Mark P.; O’Connor, Nessa (Frontiers in Marine Science, 2019)
Macroalgae are of increasing interest for high-value biotechnological applications, but some seaweeds, such as coralline red algae, cannot be grown in cultivation cost-effectively. Wild harvesting of seaweeds, particularly of those that are ecosystem engineers, must be demonstrably sustainable: here we address the topic of resource sustainability in the context of harvesting Corallina officinalis in Ireland for bioceramics. C. officinalis provides habitat for a diverse macrofaunal community and the effects of harvesting C. officinalis on the associated fauna must be included in any assessment of harvesting sustainability. Corallina intertidal turfs subject to experimental harvesting were confirmed, using DNA barcoding with cox1, to comprise only C. officinalis and not the pseudocryptic species C. caespitosa, despite the wide range of morphologies, and they had high genetic diversity. Harvesting of C. officinalis was carried out at experimental sites by two techniques (hand cutting and pulling) to test the recovery of the primary resource and the associated macroinvertebrate assemblage. Harvesting the alga by both methods encouraged regrowth: cut and pulled plots had a much higher growth rate than unharvested turfs, regaining their original length within 4-6 months of harvesting, suggesting that turfs of this species may grow to a predetermined length. The structure, richness and evenness of the invertebrate assemblage were not significantly affected by harvesting C. officinalis by cutting or pulling, though some organisms within the community showed a response to harvesting. The pattern of recovery of the sediment, an important component of the C. officinalis habitat, was consistent with the shorter (harvested) turf trapping more sediment than longer natural turfs. As many of the organisms associated with the habitat use the sediment for food or building materials, this may have ameliorated the effects of harvesting on the community. A period of a year between harvests is recommended to allow the C. officinalis biomass to return to baseline levels and unharvested fallow areas should be included in a harvesting plan to allow macroinvertebrates to re-colonise the harvested turf.